HUBUNGAN SEBARAN GERAKAN TANAH DENGAN KELURUSAN STRUKTUR GEOLOGI BERDASARKAN INTERPRETASI CITRA LANDSAT DI DAERAH KEBUMEN JAWA TENGAH - Nur, Arief Mustofa; Ansor, Chusni; Purnami, Dwi Novi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
Land movements or landslides represent one of the geologic hazards. It is often occur in Indonesia including Kebumen area. Landslide is much related with geologic lineament. The aim these study to know the relation between landslides with geologic lineament. Landslide distribution is obtained by field survey; geologic lineament is obtained by interpretation of digital TM land sat. Dominantly, the geologic lineaments of this area are northwest – southeast ward and southwest – northeast ward. Those are related with tectonic. Most of landslide occurrences at research area reside at geologic linement zona. Landslide also influenced by slope, lithology, landuse and rainfall. Landslide type in research area is creeping, slump, debris slide, debris fall, rock slide, rock fall, earth slip, and subsidence. Research area has high potentiality of landslide; it is done mitigation.